Exploring Bilingual Education Program at Private Islamic Boarding School - Fakhrudin, Mohammad Umar; Solihah, Yuni Alawaturrohmah; Kartika , Viar Dwi; Jamila (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
This case study aims to explore the process of curriculum design and development in bilingual program at private Islamic boarding school in Brebes The data were collected from stakeholders, English teachers, the members, and Self-Development Club, through direct observation, site visits, interviews, and document analysis. The data were analyzed qualitatively. There are three modifications of the curriculum supporting bilingual students' English improvements. They are implementing four years of study that the students will have a matriculation grade in the first year; adding English school hours in each grade, and providing English supporting programs named School Outing Program, Teaching Program, and Malhikdua Explore. Then, the existence of students' bilingual organization called Self-Development Club significantly contributes by taking over students' language improvement activities besides school hours. After being facilitated with the programs mentioned, the student's English proficiency was assessed through TOEFL by a certified state university language center and LPKS by the Brebes Department of Employment, with average scores of 510 (TOEFL) and 83% Grade A (LPKS). As a result, bilingual program of MA Al Hikmah 2 has successfully designed a proper curriculum to enhance students’ English proficiency.